Assessment of Knowledge, Attitude and Experiences towards Conducting Research: A Cross Sectional Study among Physiotherapists in Nigeria - Abiola O. Fafolahan; Daniel D. Ajao (Archives of Current Research International, 2022)
Aim: The aim of this study was to investigate the knowledge, attitudes and experiences towards conducting research among Physiotherapists in Nigeria. This study also aim to determine the main barriers and challenges associated with research participation Methods: A total of 207 Physiotherapists in Nigeria participated in this cross sectional study. A web based questionnaire with Uniform resource Locator (URL) link was shared on various Physiotherapy social media platforms (Facebook, WhatsApp, Telegram and Twitter). All responses were collated in Google sheets. Results: The findings of this study revealed good knowledge (87.9%) and attitude (59.4%) towards conducting research among Physiotherapists in Nigeria. There was also fair level of participation in research as only 42% were currently involved in research. The top barriers for conducting research were financial support (97.5%), statistical support (88.1%) and research training and skill (86.1%). 87.9% reported to have participated in writing a medical research at some point, only 49.8% read medical journals consistently, only 42.0% have published a research paper in a medical journal. There was significant difference between level of age and age among participants (P=0.015). The level of knowledge however didn’t differ among gender (P=0.111). There was significant association between participants who did research methodology in undergraduate, currently involved in research and level of knowledge (p=0.05, 0.004). Conclusions: Physiotherapists in Nigeria have good knowledge and attitude towards research but participation was fair. Level of knowledge differs across different age group. Financial support was the major barrier towards conducting research among Physiotherapists in Nigeria.